Employee Empowerment, Job Crafting, and Work Performance: Study on Modern Management Practices in Service - Berlian, Sucma; Hartono, Sri; Yusuf, Ramdan; Putra, Dios Nugraha (Journal Management & Economics Review (JUMPER), 2025)
This study investigates the influence of employee empowerment and job crafting on work performance within service industries adopting modern management practices. Using a quantitative research design and survey data from 350 service employees, the study examines the direct effects of empowerment and job crafting on performance, as well as the mediating role of job crafting in the empowerment–performance relationship. The results show that employee empowerment significantly enhances work performance and strongly predicts job crafting behaviors. Job crafting also demonstrates a substantial positive effect on performance, highlighting its strategic importance as a proactive work behavior that enables employees to adapt their roles to organizational demands. Mediation analysis confirms that job crafting partially mediates the relationship between empowerment and performance, indicating that empowered employees are more likely to redesign their work in ways that enhance effectiveness. These findings contribute to the integration of empowerment theory and job crafting frameworks, offering theoretical insights and practical implications for improving employee adaptability, motivation, and productivity in service organizations. The study emphasizes the need for empowerment-oriented leadership and organizational support for proactive job redesign practices to foster a resilient and high-performing workforce.